A Disintegrin and Metalloprotease-17 Regulates Pressure Overload–Induced Myocardial Hypertrophy and Dysfunction Through Proteolytic Processing of Integrin β1. Issue 4 (October 2016) - Fan, Dong; Takawale, Abhijit; Shen, Mengcheng; Samokhvalov, Victor; Basu, Ratnadeep; Patel, Vaibhav; Wang, Xiuhua; Fernandez-Patron, Carlos; Seubert, John M.; Oudit, Gavin Y.; Kassiri, Zamaneh
Abstract : A disintegrin and metalloprotease-17 (ADAM17) belongs to a family of transmembrane enzymes, and it can mediate ectodomain shedding of several membrane-bound molecules. ADAM17 levels are elevated in patients with hypertrophic and dilated cardiomyopathy; however, its direct role in hypertrophic cardiomyopathy is unknown. Cardiomyocyte-specific ADAM17 knockdown mice (ADAM17 flox/flox /αMHC-Cre; ADAM17 f/f /Cre) and littermates with intact ADAM17 levels (ADAM17 f/f ) were subjected to cardiac pressure–overload by transverse aortic constriction. Cardiac function/architecture was assessed by echocardiography at 2 and 5 weeks post transverse aortic constriction. ADAM17 knockdown enhanced myocardial hypertrophy, fibrosis, more severe left ventricular dilation, and systolic dysfunction at 5 weeks post transverse aortic constriction. Pressure overload–induced upregulation of integrin β1 was much greater with ADAM17 knockdown, concomitant with the greater activation of the focal adhesion kinase pathway, suggesting that integrin β1 could be a substrate for ADAM17. ADAM17 knockdown did not alter other cardiomyocyte integrins, integrin α5 or α7, and HB-EGF (heparin-bound epidermal growth factor), another potential substrate for ADAM17, remained unaltered after pressure overload. ADAM17-mediated cleavage of integrin β1 was confirmed by an in vitro assay. Intriguingly, ADAM17 knockdown did not affect the myocardial hypertrophy induced by a subpressor dose of angiotensin II, which occurs independent from the integrin β1–mediated pathway. ADAM17-knockdown enhanced the hypertrophic response to cyclic mechanical stretching in neonatal rat cardiomyocytes. This study reports a novel cardioprotective function for ADAM17 in pressure overload cardiomyopathy, where loss of ADAM17 promotes hypertrophy by reducing the cleavage of cardiac integrin β1, a novel substrate for ADAM17. This function of ADAM17 is selective for pressure overload–induced myocardial hypertrophy and dysfunction, and not agonist-induced hypertrophy. Abstract : Supplemental Digital Content is available in the text.